2021
DOI: 10.1016/j.abd.2020.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum levels of C-reactive protein, D-Dimer and Autologous Serum Skin Test in patients with Chronic Spontaneous Urticaria in a Brazilian tertiary center : a cross-sectional study

Abstract: Background The pathophysiology of urticaria is still poorly understood. Recent studies demonstrate that the activation of coagulation is correlated with the clinical activity of Chronic Spontaneous Urticaria. Coagulation and inflammation are strongly linked. Objectives To correlate the severity and activity of Chronic Spontaneous Urticaria with the levels of D-dimer, C-reactive protein, and autologous serum test in patients with Chronic Spontaneous Urticaria. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…This activation of platelets is thought to be related to the chemokines IL-8, GROα, and ENA-78 [14]. A few studies have reported that platelet indices such as D-Dimer show signi cant changes in CSU patients in correlation with clinical severity, autoreactivity, and/or in ammatory status [24]. In our data, a decrease in IL-8, GROα, and ENA-78 in correlation with treatment and their correlation with D-dimer value suggest that platelet activation could be more involved in the CSU pathogenesis in cases over 45 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…This activation of platelets is thought to be related to the chemokines IL-8, GROα, and ENA-78 [14]. A few studies have reported that platelet indices such as D-Dimer show signi cant changes in CSU patients in correlation with clinical severity, autoreactivity, and/or in ammatory status [24]. In our data, a decrease in IL-8, GROα, and ENA-78 in correlation with treatment and their correlation with D-dimer value suggest that platelet activation could be more involved in the CSU pathogenesis in cases over 45 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…CRP may show divergent values in chronic spontaneous urticaria (median 4.5 mg/L, and approx. 36 mg/L in another study); it can be elevated in 1/3 of cases, and it can also be correlated with treatment efficacy, while other authors have demonstrated that CRP levels were higher in those with a positive autologous serum skin test, concluding that autoimmune urticaria is characterized by low-grade inflammation, while other data have found no association between CRP and the condition [ 463 , 464 , 465 , 466 , 467 ]. Moreover, a study reported a significant association between hsCRP and uremic pruritus in chronic hemodialysis patients [ 468 ].…”
Section: Current Evidence On C-reactive Protein and Potential Conditionsmentioning
confidence: 91%
“…It was observed that 32.7% of patients required 3 or more medications to achieve CSU remission during follow-up. 15 CRP is produced by the liver and is a sensitive serum marker of inflammation. It is elevated in several diseases, including infections, neoplasms, autoimmune diseases, cardiovascular diseases, and gastrointestinal diseases.…”
Section: Disease Severity and Durationmentioning
confidence: 99%
“…Positive ASST is correlated with the presence of IgG anti-FcεRI and IgG anti-IgE antibodies, responsible for type IIb autoimmune CSU (aiCSU), whose diagnostic criteria are as follows: (a) a positive in vitro bioassay demonstrating autoantibody functionality (basophil histamine release assay [BHRA] or basophil activation marker expression, such as CD63 or CD203c by flow cytometry); (b) positive autoreactivity (a positive ASST) demonstrating the in vivo relevance of mast cell degranulation and increased capillary permeability; and (c) a positive immunoassay for autoantibodies against FcεRIα (Western blot or ELISA) demonstrating autoantibody specificity. 25 Positive ASST has been associated with greater disease activity, longer duration, and basopenia, 15,26,27 but further studies are needed. A systematic review of parameters associated with CSU duration and severity found 8 studies demonstrating an association between positive ASST and CSU severity, and 8 studies reporting no association.…”
Section: Disease Severity and Durationmentioning
confidence: 99%